Use of hydraulic modeling to evaluate hose systems - Ścieranka, Grzegorz (Instal, 2022)
The paper presents hydraulic calculations results of an exemplary hose systems with the use of hydraulic modeling in EPANET software. The relationship between the K coefficient of hydrants and the C emitter coefficient used to simulate leak flow in EPANET was determined. It has been shown that the calculation method has an impact on the hydraulic parameters of the water source.
Keywords: hose system; hydraulic calculations